ANALISIS MUQADDIMAH MUHAMMAD SYUKRI UNUS DALAM KITAB IS’AFUL KHOID FI ILMI AL-FARAIDH - Jaidi, Muhammad (Institut Agama Islam Darul Ulum Kandangan, 2023)
Abstract: This study examines a Malay-language book authored by one of the famous scholars who is still alive in Banjarmasin. The book is Is'aful Khoid Fi Ilmi Al-Faraidh, a translation into Malay of the book Tuhfah As-Saniyyah Fi Ahwal Al-Waratsatil Arba'iniyyah authored by Shaykh Hasan Muhammad Al-Masysyath Al-Makki. In addition to being translated into Malay, there are also additional explanations and procedures in calculating inheritance. This research is a library research. The subject is a number of literatures related to the problem under study. The object of this research is the analysis of muqaddimah in the book Is'aful Khoid Fi Ilmi Al-Faraidh which discusses the science of faraidh or the science of inheritance. This research produces findings, namely that in the muqaddimah of the book Is'aful Khoid Fi Ilmi Al-Faraidh there is an explanation of the science of faraidh in the form of definitions, urgency, virtues, sources, laws, concise examples, pillars, conditions, causes, and barriers in Islamic inheritance.